(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the relationship between moral philosophy and aesthetic experience in the Enlightenment novel. Focusing on the intellectual climate of the eighteenth century, the study explores how novelists combined ethical instruction with artistic form in order to shape readers’ moral sensibilities. Enlightenment thinkers believed that literature could educate individuals through reason, sentiment, and imagination. By analyzing selected novels of the period, the article demonstrates how narrative structure, character development, and emotional engagement functioned as tools for moral reflection. The study argues that the Enlightenment novel represents a unique synthesis of philosophy and art, where aesthetic pleasure and moral education operate together to promote rationality, virtue, and social harmony.